Comparative CT with stress manoeuvres for diagnosing distal isolated tibiofibular syndesmotic injury in acute ankle sprain: a protocol for an accuracy- test prospective study. Issue 9 (3rd September 2020) - Rodrigues, João Carlos; Santos, Alexandre Leme Godoy; Prado, Marcelo Pires; Alloza, José Felipe Marion; Masagão, Renato Amaral; Rosemberg, Laercio Alberto; Barros, Durval do Carmo Santos; Castro, Adham do Amaral e; Demange, Marco Kawamura; Lenza, Mario; Ferretti, Mario
Abstract : Introduction: Although several imaging options are available for diagnosing syndesmotic injury, a fundamental question that guides treatment remains unanswered. Syndesmotic instability is still challenging to diagnose correctly, and syndesmotic disruption and true syndesmotic instability should be differentiated. Currently, imaging tests quickly diagnose severe syndesmotic instability but have difficulty in diagnosing mild and moderate cases. This study aims to investigate which strategy among an existing CT index test and two new add-on CT index tests with stress manoeuvres more accurately diagnoses syndesmotic instability. The secondary objective is to investigate the participants' disability outcomes by applying the Foot and Ankle Ability Measure questionnaire. Methods and analyses: This study of a diagnostic accuracy test will consecutively select individuals older than 18 years with a clinical diagnosis of a suspected acute syndesmotic injury. Three strategies of the CT index test (one in the neutral position and two with stress) will examine the accuracy using MRI as the reference standard. The external rotation and dorsiflexion of the ankle will guide the stress manoeuvres. A comparison of measurements between the injured syndesmosis and the uninjured contralateral side of the same individual will investigate the syndesmotic instability, by evaluating the rotational and translational relationships between the fibula and tibia. Sensitivity, specificity, area under the receiver operating characteristic curve and likelihood analyses will compare the diagnostic accuracies of the strategies. Ethics and dissemination: The Internal Review Board and the Einstein Ethics Committee approved this study (registered number 62100016.5.0000.0071). All participants will receive an oral description of the study's aim, and the choice to participate will be free and voluntary. Participants will be enrolled after they sign the written informed consent form, including the terms of confidentiality. The results will be presented at national and international conferences and published in peer-reviewed journals and social media. Trial registration number: ClinicalTrials.gov Registry (NCT04095598 ; preresults).